Pengaruh Penerapan Strategi Pembelajaran Giving Question And Getting Answer Terhadap Peningkatan Kompetensi Strategis Matematis pada Siswa SMK - Dian Nursopiah; Marthen Tapilouw; Irmawan (EDUCARE, 2014)
This research was conducted to obtain empirical evidence about the effect of applying Giving Question and Getting Answer learning strategies to improve mathematical strategic competencies in vocational students. The research method used was quasi-experimental research conducted on students of class X in one of the Vocational Schools in Bandung. This study used a non-equivalent control group research design. In this study the properties used are quantitative and qualitative. The results of the study explained that there was an effect of the application of Giving Question and Getting Answer learning strategies to the improvement of mathematical strategic competencies in vocational students, and described as follows: (1) There was an increase in mathematical strategic competence in students learning using Giving Question and Getting Answer learning strategies. (2) Improvement of mathematical strategic competencies between students whose learning with Giving Question and Getting Answer learning strategies is better than students who learn from conventional learning strategies.